Coexistence or Competition? China’s Evolution in Global Institutional Power - Shaoyu Yuan (Histories)
China’s engagement with global governance has evolved significantly since 1949, transitioning from outright rejection during its revolutionary isolation (1949–1971) to strategic engagement with key institutions such as the United Nations, IMF, and WTO (1971–2000), and more recently to the creation of parallel institutions like the AIIB and Belt and Road Initiative (2000–present). This paper traces these historical phases to analyze how China has navigated and reshaped global norms, balancing its integration into existing frameworks with efforts to build alternative governance structures. While Hegemonic Stability Theory and Power Transition Theory offer insights into China’s evolving strategy, neither fully encapsulates its pragmatic, adaptive approach. China’s domestic regulatory innovations, such as the Social Credit System and its promotion of cyber sovereignty, increasingly influence its global governance initiatives, reflecting a deliberate effort to export its governance models. Rather than fully integrating into or replacing the U.S.-led liberal order, China employs a dual-track strategy: engaging with global institutions where advantageous while promoting state-centric alternatives to liberal norms. This study argues that China’s historical trajectory underscores its pivotal role in shaping a multipolar world order, where competing governance frameworks coexist and challenge the dominance of Western-led institutions.